La encíclica apócrifa de León XIII: un episodio del anticlericalismo latinoamericano - Hernández Aponte, Gerardo Alberto (Universidad de San Buenaventura - Cali, 2017)
This paper describes and analyzes an event apparently hitherto ignored by ecclesiastical historiography. I am referring to the publication of an apocryphal encyclical of Pope Leo XIII by several latinamerican newspapers in 1899. This paper is primarily a proposal to study the repercussions the pseudo document had in different countries in order to then be able to have a total view of the matter.